2008
DOI: 10.1080/17470910701458551
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates for observing and imagining non-object-directed actions

Abstract: The present fMRI study was aimed at assessing the cortical areas active when individuals observe non-object-directed actions (mimed, symbolic, and meaningless), and when they imagine performing those same actions. fMRI signal increases in common between action observation and motor imagery were found in the premotor cortex and in a large region of the inferior parietal lobule. While the premotor cortex activation overlapped that previously found during the observation and imagination of object-directed actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 50 publications
4
58
0
2
Order By: Relevance
“…unlike in monkeys, the parieto-frontal mirror circuit of humans also becomes active during the observation of individual movements [55][56] . The initial evidence for this mechanism was based on TMS experiments which indicated that the observation of the movements of others results in an activation of the muscles involved in the execution of those movements [32][33][34][35][36] .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%
“…unlike in monkeys, the parieto-frontal mirror circuit of humans also becomes active during the observation of individual movements [55][56] . The initial evidence for this mechanism was based on TMS experiments which indicated that the observation of the movements of others results in an activation of the muscles involved in the execution of those movements [32][33][34][35][36] .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%
“…First, avoidance behavior is likely to be triggered by disgusting stimuli, too. Second, the pattern of parietal activation does not seem to be specific to upper arm movement planning or imagery (Ruby and Decety, 2003;Lui et al, 2008a). Third, they are not accompanied by a specific premotor/posterior parietal cortex activation.…”
Section: Brain Regions Involved In the Observation Of Unpleasant Stimulimentioning
confidence: 99%
“…However, the majority of this literature investigated only one mode of covert movement mode or, at most, compared two modes, usually motor imagery and observation (Clark et al, 2003;Filimon et al, 2007;Iseki et al, 2008;Lui et al, 2008;Macuga and Frey, 2012;Munzert et al, 2008;Piefke et al, 2009;Roosink and Zijdewind, 2010;Wang et al, 2008). Therefore inferences between studies have to be made when comparison between all modes of covert movement is to be conducted.…”
Section: Introductionmentioning
confidence: 99%